POLA PENYELESAIAN SENGKETA TANAH ULAYAT DI SUMATERA BARAT (Sengketa antara Masyarakat vs Pemerintah) - Kurnia Warman & Syofiarti (Masalah-Masalah Hukum, 2012)
Abstract Using of communal land by private enterprise has been also creating disputes in West Sumatra. The disputes are started from the unprocedure land procurement process. According to the law of land procurement in Indonesia, for getting land, a private enterprise should contact the land owners (or traditional communities) as the subject of communal land for making contract directly. As a matter of fact, they have got the land from the Local Government not from the people. The communities protested to the corporate activities on their land. Beside that, the private enterprises have got agrement with communities, but they did not follow it, for instance building plasma plantation for the communities. Key Word: disputes of communal land Abstrak Penggunaan tanah ulayat oleh para investor di Sumatera Barat, seringkali menimbulkan sengketa. Hal ini disebabkan karena penggunaannya tidak sesuai dengan yang seharusnya. Menurut hukum pertanahan di Indonesia, penggunaan lahan oleh para investor harus berhadapan langsung dengan pemilik tanah atau masyarakat adat sebagai pemilik hak ulayat dengan melaksanakan perjanjian. Pada kenyataannya, para investor justru langsung mendapatkan tanah tersebut melalui Pemerintah. Akibatnya masyarakat sebagai pemilik mengajukan protes atas kegiatan investor di atas tanah mereka yang kemudian hal ini memicu timbulnya sengketa tanah ulayat. Kata Kunci : sengketa tanah ulayat